Resveratrol Sensitizes Carfilzomib-Induced Apoptosis via Promoting Oxidative Stress in Multiple Myeloma Cells - Li, Qian; Yue, Yuanfang; Chen, Lin; Xu, Chang; Wang, Yan; Du, Liqing; Xue, Xiaolei; Liu, Qiang; Wang, Yafei; Fan, Feiyue (Frontiers in Pharmacology, 2018)
Abstract The proteasome inhibitor is a target therapy for multiple myeloma (MM) patients, which has increased the overall survival rate of multiple myeloma in clinic. However, relapse and toxicity are major challenges for almost all MM patients. Thus, there is an urgent need for an effective and less toxic combination therapy. Here, we demonstrated that a natural compound, resveratrol (RSV) displayed anti-proliferative activity in a dose- and time-dependent manner in a panel of MM cell lines. More importantly, a low concentration of RSV was synergistic with a low dose of the proteasome inhibitor carfilzomib (CFZ)to induce apoptosis in myeloma cells. Further studies showed that mitochondria was a key regulatory site after RSV/CFZ combination treatment. RSV induced the release of second mitochondria-derived activator of caspase (Smac) in a dose-dependent manner and kept the Smac in a high level after combination with CFZ. Also, RSV was additive with CFZ to increase reactive oxygen species (ROS) production. Moreover, a stress sensor SIRT1, with deacetylase enzyme activity, was remarkably downregulated after RSV/CFZ combination, thereby significantly decreasing its target protein, survivin in MM cells. Simultaneously, autophagy was invoked after RSV/CFZ combination treatment in myeloma cells. Further inhibition of autophagy could increase more ROS production and apoptosis, indicating a close linkage between autophagy and proteasome to modulate the oxidative stress. Together, these findings suggest that induction of multiple stress responses after RSV/CFZ combination is a major mechanism to synergistically inhibit MM cell growth and reduce the toxicity of CFZ in MM cells. This study also provides an important rationale for the clinic to consider an autophagy inhibitor for the combination therapy in MM patients.